Angiographic and Histologic Analysis of Experimental Aneurysms Embolized with Platinum Coils, Matrix, and HydroCoil - Ding, Yong Hong (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: A report directly comparing platinum coils, Matrix coils, and HydroCoils in a single animal model does not currently exist. We evaluated and compared the performance of these three products in the embolization of experimental aneurysms. METHODS: Thirty-three elastase-induced saccular aneurysms were created in rabbits. Aneurysms were embolized with Matrix coils (n = 15), HydroCoils (n = 9), or platinum coils (n = 9). The groups were compared with respect to the following parameters: aneurysm size, procedure duration, number and total length of devices deposited, angiographic occlusion score, and volumetric occlusion percentage. Follow-up angiographic and histologic features at 2, 6, and 10 weeks after embolization were analyzed. Groups were compared by using analysis of variance and χ(2) tests. RESULTS: No significant differences were found among groups regarding aneurysm size, total device length, initial angiographic occlusion score, or procedure time. The mean number of devices for Matrix subjects was less than that for platinum coils (P = .02) and HydroCoil (P = .03). Volumetric occlusion for HydroCoil (76%) was significantly greater (P < .0001) than both platinum coils (31%) and Matrix (23%). Angiographic durability was significantly increased in the HydroCoil group compared with Matrix (P = .03). Coil compaction was found more frequently in the Matrix group (five cases, 33%) than the HydroCoil (no cases, 0%), or platinum coil groups (two cases, 22%). The Matrix group showed greater tissue reaction compared with platinum coils (P < .05). CONCLUSION: In the rabbit model, the use of HydroCoils results in improved long-term occlusion rates compared with Matrix and platinum coils. The Matrix group showed an increase in inflammation and coil compaction compared with HydroCoils and platinum coils.